(untitled) (Revista Venezolana de Salud Pública, 2019)
The poor diet and absence of minimal sanitary elements, in the populations of Ologá and Congo Mirador, make their inhabitants susceptible to suffer from a diversity of mainly infectious and nutritional diseases, which alert the need to address these problems in a constant and sustained manner.